2022
DOI: 10.1021/acs.est.2c03099
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Halogenated Polycyclic Aromatic Hydrocarbons in the Serum of Coal-Fired Power Plant Workers: Levels, Sex Differences, Accumulation Trends, and Risks

Abstract: Workers in coal-fired power plants are at a high risk of exposure to polycyclic aromatic hydrocarbons (PAHs) and their halogenated derivatives (HPAHs), yet no studies have investigated such exposure of HPAHs. In this study, 12 PAHs and 8 chlorinated PAHs, but no brominated PAHs, were detected in >80% of serum samples from workers of a coal-fired power plant in eastern China. Serum HPAH concentrations were higher in plant workers (16–273 ng/g lipid) than in people without occupational exposure (12–51 ng/g lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…These workers have been shown to have higher concentrations of serum HPAHs than those without such occupational exposure. 75 In the field of road paving, skin contact with PAH derivatives has been thoroughly examined, revealing elevated levels of certain APAHs (such as 1-methylphenanthrene and 2,10/4,10dimethylphenanthrene) on the skin of road pavers, surpassing the amounts of parent PAHs. 76 Security guards working near heavy traffic are also subject to occupational exposure to OPAHs, as evidenced by a significant increase in oxidative stress markers following an 8 h shift.…”
Section: Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…These workers have been shown to have higher concentrations of serum HPAHs than those without such occupational exposure. 75 In the field of road paving, skin contact with PAH derivatives has been thoroughly examined, revealing elevated levels of certain APAHs (such as 1-methylphenanthrene and 2,10/4,10dimethylphenanthrene) on the skin of road pavers, surpassing the amounts of parent PAHs. 76 Security guards working near heavy traffic are also subject to occupational exposure to OPAHs, as evidenced by a significant increase in oxidative stress markers following an 8 h shift.…”
Section: Derivativesmentioning
confidence: 99%
“…One recent study did report the parent compound levels of XPAHs in a workplace exposure assessment, yet as previously illustrated, the mere quantification of the parent compound may not adequately represent the accurate internal exposure levels to exogenous chemicals such as PAHs and their derivatives. 75 ■ TOXICITY OF PAH DERIVATIVES Numerous prior investigations have indicated that PAH derivatives may exert toxic effects as significant as, or surpassing, their unsubstituted parent compounds. Exposure to these derivatives may precipitate a variety of detrimental effects, such as death, carcinogenicity, immunotoxicity, and developmental toxicity, principally through metabolic activation (introduced in previous section) and the involvement of the AhR signaling pathways.…”
Section: Derivatives and Potential Exposure Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Polycyclic aromatic hydrocarbons (PAHs) are a series of persistent organic pollutants (POPs) with potential toxicity and health risks on the biosystem and ecosystem . Halogenated PAHs are the derivatives of PAHs, and they are considered as the emerging POPs with higher toxicities and more risks than PAHs. , Accurate, sensitive, in situ, and real-time analysis of trace PAHs and halogenated PAHs in complex samples can provide crucial information to understand their environmental distribution and ecological risks. Gas chromatography (GC) coupled with mass spectrometry (MS) has been recognized as the most conventional method for analysis of PAHs and halogenated PAHs .…”
mentioning
confidence: 99%